2016
DOI: 10.1007/s10147-016-1033-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a novel endothelial marker, C-type lectin 14A, in epithelial ovarian cancer and its prognostic significance

Abstract: This study demonstrates MVD as detected by CLEC14A in EOC. Treatment with chemotherapy reduces tumor blood vessels significantly. We suggest that CLEC14A may be a more specific endothelial marker to assess tumor angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Clec14A expression is considered endothelial specific. Interestingly, the expression of Clec14A is barely detectable in healthy vessels but strongly upregulated in angiogenic tumor-associated blood vessels of non-small cell lung cancer and ovarian cancer tissues [ 15 , 16 ]. It has been found to regulate EC tube formation and migration in vitro as well as tumor angiogenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Clec14A expression is considered endothelial specific. Interestingly, the expression of Clec14A is barely detectable in healthy vessels but strongly upregulated in angiogenic tumor-associated blood vessels of non-small cell lung cancer and ovarian cancer tissues [ 15 , 16 ]. It has been found to regulate EC tube formation and migration in vitro as well as tumor angiogenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently found to be upregulated at the protein level and increased with tumour progression in two different spontaneous mouse tumour models, namely cervical and pancreatic . More recently, CLEC14A overexpression on the vasculature in ovarian cancer has been reported but did not correlate with survival in this tumour type . The authors also demonstrated that CLEC14A expression was undetectable along with reductions in microvessel density in patients receiving neoadjuvant chemotherapy prior to surgery.…”
Section: Clec14amentioning
confidence: 98%
“…Recently, Noy et al reported that tumor growth and vascularity was reduced in a CLEC14a-knockout syngeneic tumor mouse model, compared to wild-type mice [ 207 ]. More recently, Krishna et al, reported that microvessel density, detected using an anti-CLEC14a antibody, was significantly reduced in patients with epithelial ovarian cancer treated with chemotherapy, suggesting that CLEC14a may be a more specific endothelial marker to assess tumor angiogenesis [ 211 ]. Collectively, this evidence suggests that CLEC14a may be a novel tumor endothelial cell-specific marker of tumor angiogenesis and a central regulator of tumor angiogenesis.…”
Section: Clec14a Signalingmentioning
confidence: 99%